THE EFFECT OF SERVICE QUALITY AND CUSTOMER VALUE ON CUSTOMER SATISFACTION AND CUSTOMER LOYALTY IN BANK SULTRA - Abdul Razak; Abdul hakim; Asraf Yunus (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
The purpose of this study was to determine and analyze the effect of service quality and customer value on satisfaction and loyalty, the effect of satisfaction on loyalty and the role of satisfaction in mediating the relationship between service quality and customer value on loyalty to Bank Sultra customers. Analysis of data processing using Structural Equatation Model (SEM) with Lisrel software. SEM analysis is more effectively used to examine the effect of complex variables even involving mediating variables. The object of this research is the customer of Bank Sultra in Southeast Sulawesi Province. The types of data in this study are primary data and secondary data. Primary data is data taken directly from the source using a questionnaire instrument. In addition, secondary data from websites, journals, and books are also used. The results of the study found that service quality and customer value had a positive and insignificant effect on customer satisfaction but had a positive and significant effect on customer loyalty, besides satisfaction had an effect on customer loyalty and satisfaction itself was able to play a role in mediating the relationship between service quality and customer loyalty. . With regard to this finding, the researcher suggests the need to build and maintain customer loyalty with a strategy of increasing factors that are considered not optimal by customers such as reliability, responsiveness, assurance and empathy, in addition to the need to maintain and develop a high sense of belonging to the customer towards Bank Sultra by trying to emphasize to staff about the importance of building emotional relationships with customers by greeting in a friendly manner and serving politely, interacting and trying to understand the identity of the customer's background so that intimacy with customers is established. This needs to be done as a form of giving high appreciation to customers